Numerous Factors Affecting Performance of NOMA for Massive Machine Type Communications in B5G Systems - Yan, Chunlin; Liu, Wei; Yuan, Hongwei (Frontiers in Communications and Networks, 2021)
Massive machine type communications (mMTC) is one of the critical requirement for beyond fifth generation (B5G) communication systems. Services for huge number of user terminals should be provided simultaneously due to the explosive developing of mMTC. It is proved that non-orthogonal multiple-access (NOMA) is effective in satisfying such requirement. In this paper we evaluate the impacts of numerous factors, such as channel encoding, channel decoding, repetition number, multi-user detector and number of receiver antennas, on the performance of NOMA. It is surprised to find that some conclusions drawn from orthogonal multiple access system may be invalid for NOMA systems. The factors which have significant impact on the performance of NOMA should be paid more attention to in the system design. The analysis and evaluation results shine more light on how to design an effect NOMA scheme by considering both transmitter and receiver to fulfill the requirements of mMTC for B5G systems.